When the sergeant came marching home - Lemna, Don, 1936- (New York : Holiday House, 2008)
When his father returns from the war in 1946, a ten year old boy and his family move from their home in a Montana town to an old, run-down farm in the middle of nowhere where they work hard trying to make ends meet.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
5.7
3-6
Keywords: Families -- Montana -- Juvenile fiction; Farm life -- Montana -- Juvenile fiction; Family life -- Fiction; Farm life -- Fiction; Historical fiction; Family life -- Montana -- Fiction; Farm life -- Montana -- Fiction; Historical fiction; Montana -- History -- 20th century -- Juvenile fiction; Montana -- History -- Fiction; Montana -- History -- Fiction; Historical fiction